Non-Catalytic and MgSO4 - Catalyst based Degradation of Glycerol in Subcritical and Supercritical Water Media - Yuniati, Yuyun; Sumarno, Sumarno; Mahfud, Mahfud (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2011)
This research aims to study the glycerol degradation reaction in subcritical and supercritical water media. The degradation of glycerol into other products was performed both with sulphate salt catalysts and without catalyst. The reactant was made from glycerol and water with the mass ratio of 1:10. The experiments were carried out using a batch reactor at a constant pressure of 250 kgf/cm2, with the temperature range of 200-400oC, reaction time of 30 minutes, and catalyst mol ratio in glycerol of 1:10 and 1:8. The products of the non-catalytic glycerol degradation were acetaldehyde, methanol, and ethanol. The use of sulphate salt as catalyst has high selectivity to acetaldehyde and still allows the formation alcohol product in small quantities. The mechanism of ionic reaction and free radical reaction can occur at lower temperature in hydrothermal area or subcritical water. Conversion of glycerol on catalytic reaction showed a higher yield when compared with the reaction performed without catalyst